Introdução do minerador de superfície (Sistema de lavra contínua) na mina de bauxita, Paragominas - PIMENTEL, Edil Neto (2019)
The mining system used at Paragominas Mining has, over the years, undergoing a series of changes and adaptations, seeking not only reduce operating costs, but operations that not violate the environment and provide safer conditions for employees. It is focused on this action line that will present an initial assessment of surface mining operations (SM 2500) in current conditions of Paragominas Bauxite Mine (without addressing equipment maintenance rates) and thereby compare their production rates with conventional mining system used previously. At the moment, the work is not intended to detail the entire system of unit operations performed by the Management Operating Mine (GAOMP), but only those related to the process of bauxite mining (scarification, grading, loading, transport and scraping the pit bottom) compared to the SM 2500 technology.